Expanding the Distributed Generation Concept: Toward Decentralized Energy and Water Supply - Ciriminna, Rosaria (Glob Chall, 2018)
Rainwater harvesting decentralizes the water supply in full analogy to what building‐integrated photovoltaics and solar thermal do for electricity and heat. In this new decentralized generation scenario, the built environment is used to collect both sunlight photons and water molecules with significant economic and environmental benefits. Referring to recent progress and to real‐life findings from around the world, this work provides an answer to several relevant questions of direct interest to policy makers and early adopters of broadened distributed generation. The conclusions offer guidelines for developing a successful distributed generation strategy at the regional level by unifying solar energy and water management policies.